Non-Steroidal Anti-Inflammatory Drugs and Aspirin Therapy for the Treatment of Acute and Recurrent Idiopathic Pericarditis - Nicholas Schwier; Nicole Tran (MDPI AG, 2016)
Aspirin (ASA) and non-steroidal anti-inflammatory drugs (NSAIDs) are a mainstay of therapy for the treatment of idiopathic pericarditis (IP). A comprehensive review consisting of pertinent clinical literature, pharmacokinetic, and pharmacodynamic considerations, has not been released in recent years. This review will facilitate the clinician's understanding of pharmacotherapeutic considerations for using ASA/NSAIDs to treat IP. Data were compiled using clinical literature consisting of case reports, cohort data, retrospective and prospective studies, and manufacturer package inserts. ASA, ibuprofen, indometacin, and ketorolac relatively have the most evidence in the treatment of IP, provide symptomatic relief of IP, and should be tapered accordingly. ASA is the drug of choice in patients with coronary artery disease (CAD), heart failure (HF), or renal disease, but should be avoided in patients with asthma and nasal polyps, who are naïve to ASA therapy. Ibuprofen is an inexpensive and relatively accessible option in patients who do not have concomitant CAD, HF, or renal disease. Indometacin is not available over-the-counter in the USA, and has a relatively higher incidence of central nervous system (CNS) adverse effects. Ketorolac is an intravenous option; however, clinicians must be mindful of the maximum dose that can be administered. While ASA/NSAIDs do not ameliorate the disease process of IP, they are part of first-line therapy (along with colchicine), for preventing recurrence of IP. ASA/NSAID choice should be dictated by comorbid conditions, tolerability, and adverse effects. Additionally, the clinician should be mindful of considerations such as tapering, high-sensitivity CRP monitoring, bleeding risk, and contraindications to ASA/NSAID therapy.